Padrões e tendências de morbimortalidade e sobrevida em crianças com AIDS no Brasil - Ramos Júnior, Alberto Novaes (2011)
HIV/AIDS infection among children is in the process of being eliminated as a public health problem in high-income countries, but still maintains an elevated level of morbidity-mortality in developing nations. Brazil stands out for its consistent HIV/AIDS control policy, particularly its adoption of free and universal distribution of HAART in 1996. This thesis describes the patterns and trends of morbidity-mortality and survival in children with AIDS in Brazil. Two analytical groupings were formed: 1) national studies of AIDS morbidity-mortality in children, 2) national survival studies in children with AIDS. In the first group, an ecological time-series study was undertaken (1984-2008) on cases (14,314) and deaths (5,041) from AIDS in Brazil by region and age group (0-12 and 0-4 years), based on an analysis of the respective rates using polynomial regression, percentage differences and ratios in the pre-HAART and HAART eras. In addition, a temporal trend analysis was done (1999-2007) on mortality from the various causes related to HIV/AIDS infection in children in Brazil (2,191/680,736) using Mortality Odds Ratio (MOR). Among the second group, a multi-centric, national retrospective cohort study of survival of children with AIDS (920 children, 1999-2002, until 2007) and associated factors was conducted with integrated analysis of the first national study (914 children, 1983-1998, until 2002) for verification of survival trends and occurrence patterns of late diagnosis and AIDS-defining diseases. The results point to the fact that Brazil shows a reduction of AIDS morbidity and mortality after the implementation of HAART, but with large regional disparities. The poorest regions of the country (North/Northeast) showed the worst trend for mortality (p<0.001), despite the concentration of cases and deaths in the most developed regions (South/Southeast). In terms of incidence, evolution in the Northeast stabilized (p<0.001), whereas the South showed increasing trends for children aged 0-4 (p<0.001), with the highest national rates for both age groups. The mortality rate from causes not related to HIV/AIDS between 1999 and 2007 was stable (0.08/100,000 population). The MOR indicates an increasing trend of these causes from 2000-2007 (1.18 versus 1.85), although not statistically significant (p=0.413). A trend of specific causes was not identified in this group. The probability of survival at 60 months was 0.88 (CI 95%: 0.86-0.91), with the lowest survival rates among children <1 year of age (p=0.013), category C (p<0.001), opportunistic diseases (p<0.001) and without ART (p<0.001). In the national studies there were, respectively, 420 (46%) and 109 (11.8%) deaths, with a trend for increased survival (p<0.001), varying from 0.20 (<1988) to 0.90 (2001-2002) post-HAART (0.41 versus 0.84, p<0.001). There was a reduction in late diagnosis and AIDS-defining diseases in children born (p=0.009 and p<0.001) and diagnosed post-HAART (p=0.004 and p<0.001), though with elevated frequencies still seen in the second cohort (47.7% versus 36.1% and 80.7% versus 50.8%). Bacterial diseases and pneumocystosis remained important, but to a lesser degree. It is concluded that morbidity-mortality due to AIDS among Brazilian children has been declining, principally after the adoption of HAART. Survival increased significantly to the point of making AIDS a chronic condition with inherent challenges. However, there were regional inequalities with differences in the implementation of control activities, and worse conditions in the poorest regions, still showing characteristics of the pre-HAART era. In addition, the study reveals important issues related to coverage/quality of health care for women (particularly pre-natal care and family planning) and for children exposed to or infected with HIV, as well as to the dynamics of HIV-1 transmission in Brazil.